Role of electron acceptors in soil resource circulation for organic waste composting - Suwimon Buaprom; Noppawan Semvimol; Onanong Phewnil; Thanit Pattamapitoon; Kasem Chunkao; Chulabut Chanthasoon; Watcharapong Wararam (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Soil is an important accelerator for biodegradable processes. Soil resource circulation concept by using the compost from the previous crop as cover materials for the recent composting mass was evaluated as it contained soil and amorphous Fe as an energy source. Therefore, this research was focused on the possibility and the changes in the electron acceptors in the organic waste composting process.Method The 2 experiments using different covering materials: paddy soil as a control (T1) and compost (T2) in a completely randomized design. An amount (670 g) of organic wastes was altered with 210 g of materials covered in 3 layers with 60 mL of water added every 7 days during a period of 30 days. The physico-chemical parameters, redox potential (Eh), and electrical conductivity (EC) were studied beside the basic soil parameters including electron acceptors such as NO-3, MnO2, Fe2O3, and SO4-2.Results The changes in physical and chemical properties during the degradation process were not different. The Eh reacted intensely and continuously in the same direction. The T2 compost product contained the highest SO4-2 level compared to T1 but there were no significant differences in the organic carbon and C/N ratio, though the quality of T1 was better.Conclusion Covering the organic waste with compost improved the nutrient content in the compost products. Therefore, compost can be used as a cover material instead of soil in the composting process. However, to increase the number of electron acceptors, cover materials should be mixture of soil with compost for greater efficiency.